IgG4-related disease in a multi-ethnic community: Clinical characteristics and association with malignancy - Poo,SX; Tham,CSW; Smith,C; Lee,J; Cairns,T; Galliford,J; Hamdulay,S; Jacyna,M; Levy,JB; McAdoo,S; Roufosse,C; Wernig,F; et al. (QJM: An International Journal of Medicine, 2019)
BackgroundImmunoglobulin-G4-related disease (IgG4-RD) is a recently recognised fibro-inflammatory condition that can affect multiple organs. Despite growing interest in this condition, the natural history and management of IgG4-RD remain poorly understood.AimTo describe the clinical characteristics, treatment and outcomes of IgG4-RD in a multi-ethnic UK cohort, and investigate its possible association with malignancy.DesignRetrospective analysis of case-note and electronic data.MethodsCases were identified from sub-specialty cohorts and a systematic search of an NHS trust histopathology database using ‘IgG4’ or ‘inflammatory pseudotumour’ as search terms. Electronic records, imaging and histopathology reports were reviewed.Results66 identified cases of IgG4-RD showed a similar multi-ethnic spread to the local population of North West London. The median age was 59 years and 71% of patients were male. Presenting symptoms relating to mass effect of a lesion were present in 48% of cases and the mean number of organs involved was 2.4. 10 patients had reported malignancies with 6 of these being haematological. 83% of those treated with steroids had good initial response, however 50% had relapsing-remitting disease. Rituximab was administered in 11 cases and all achieved an initial serological response. Despite this, 7 patients subsequently relapsed after a mean duration of 11 months and 4 progressed despite treatment.ConclusionsWe report a large UK-based cohort of IgG4-RD that shows no clear ethnic predisposition and a wide range of affected organs. We discuss the use of serum IgG4 concentrations as a disease marker in IgG4-RD, the association with malignant disease and outcomes according to differing treatment regimens.